2022
DOI: 10.1021/acsnano.1c04538
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Microstructure of Lamellar Ti3C2Tx MXene Aerogel by Compressive Straining

Abstract: Aerogels are attracting increasing interest due to their functional properties, such as lightweight and high porosity, which make them promising materials for energy storage and advanced composites. Compressive deformation allows the nano- and microstructure of lamellar freeze-cast aerogels to be tailored toward the aforementioned applications, where a 3D nanostructure of closely spaced, aligned sheets is desired. Quantitatively characterizing their microstructural evolution during compression is needed to all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In fact, the wavelength (λ) of the product fabricated by the freeze-drying method, which is the average wall thickness plus its adjacent macropore size, follows an empirical power-law relationship with solidification velocity (ν) as shown in eq : λ = normalA × ν n where n indicates the effect of freezing velocity on the wavelength (λ) and A refers to the attributions from the initial suspensions, such as viscosity. Because AS02, AS12, AS22, AS32, and AS62 products are fabricated at the same freezing temperature and have the same solid loading, slurry viscosity as one potential crucial variable is investigated in this work.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In fact, the wavelength (λ) of the product fabricated by the freeze-drying method, which is the average wall thickness plus its adjacent macropore size, follows an empirical power-law relationship with solidification velocity (ν) as shown in eq : λ = normalA × ν n where n indicates the effect of freezing velocity on the wavelength (λ) and A refers to the attributions from the initial suspensions, such as viscosity. Because AS02, AS12, AS22, AS32, and AS62 products are fabricated at the same freezing temperature and have the same solid loading, slurry viscosity as one potential crucial variable is investigated in this work.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Reproduced with permission. [ 118 ] Copyright 2022, American Chemical Society. g) Subvolumes of the CT data of MXene aerogels at uncompressed and 50% of compression, showing sheet spacing reduction for initially 0° orientation, while sheet spacing reduction and rotation for initially 45° orientation and the buckling structure at initially 90° orientation.…”
Section: X‐ray Techniques In Mxene Researchmentioning
confidence: 99%
“…This results in a substantial change in the microstructure, potentially closing and/or blocking the openings within the walls as the walls get closer (Figure 6e). [117] Rawson et al [118] classified the orientation of lamellar channels in MXene aerogels according to the polar angle of their sheet relative to the loading direction (Z) in 10°increments (Figure 6f). By an in situ micro-CT compression tests, they found that the predominant intradomain behavior is sheet reorientation toward the loading direction (Z) and simultaneous reduction in sheet spacing (Figure 6g).…”
Section: Microcomputed Tomography (Micro-ct)mentioning
confidence: 99%
“…On account of inherent van der Waals forces between MXene layers, MXene nanosheets have an inevitable tendency to agglomerate and repacking, which leads to substantial difficulty in the formation of all‐MXene gels; therefore, it remains a major challenge in preparing aerogels solely composed of MXene and controlling their aerogel nano‐ and microstructure. [ 28 ] To address this key issue, a number of synthetic strategies have recently been reported, providing efficient solutions in the field. For example, Zhang et al developed a template‐free method for fabricating 3D macroporous MXene‐based aerogels through vacuum filtration and rapid freezing ( Figure a).…”
Section: Design and Fabrication Of Mxene‐based Aerogelsmentioning
confidence: 99%